A dynamic estimation of board efficiency index and financial performance: evidence from China - Wu, Shizong; Saidin, Saidatunur Fauzi; Osman, Mohammad Noor Hisham; Teruki, Neilson (Human Resource Management Academic Research Society, 2024)
This study aims to evaluate the impact of the Board Efficiency Index on the financial performance of listed companies in China, from both market-based and residual income perspectives. The sample consists of 6,130 observations from 1,226 firms listed on the Shanghai Stock Exchange over the period from 2018 to 2022. The System Generalized Method of Moments (GMM) is employed to address endogeneity issues, and its effectiveness is compared with Fixed Effects and Two-Stage Least Squares (2SLS) regression models. The findings indicate that the Board Efficiency Index positively influences financial performance, suggesting that management should recognize the importance of improving board efficiency. By optimizing board structure, enhancing decision-making efficiency, and strengthening oversight capabilities, firms can achieve better governance outcomes and improve overall market performance and value. This provides empirical support for emerging markets like China. This study also focuses on comparing market value (Tobin's Q) and residual income (Economic Value-Added Rate) to explore the impact of the Board Efficiency Index. The results show that, within the dynamic interplay of corporate governance structures and financial performance, the Board Efficiency Index consistently has a positive effect on financial performance.